Antibody-dependent enhancement of porcine reproductive and respiratory syndrome virus infection downregulates the levels of interferon-gamma/lambdas in porcine alveolar macrophages in vitro - Zhang, Liujun; Feng, Xing; Wang, Huandi; He, Shaojun; Fan, Hongjie; Liu, Deyi (Frontiers in Veterinary Science, 2023)
Antibody-dependent enhancement (ADE) promotes the porcine reproductive and respiratory syndrome virus (PRRSV) invasion into the target cells through Fc receptor-mediated endocytosis. It can cause PRRSV-persistent infection among pig herds on farms. ADE has been well accepted as a primary determinant that exacerbates the disease severity in PRRSV infection. But, the effect of PRRSV-ADE infection on the natural antiviral immunity of the hosts has yet to be well investigated. Mainly, whether the ADE of PRRSV infection impacts the levels of type II (interferon-gamma, IFN-γ) and III (interferon-lambdas, IFN-λs) interferons (IFNs) remains unclear. In this study, our results showed that PRRSV significantly induced the secretion of IFN-γ, IFN-λ1, IFN-λ3, and IFN-λ4 in porcine alveolar macrophages (PAMs) in early infection and weakly inhibited the production of IFN-γ, IFN-λ1, IFN-λ3, and IFN-λ4 in PAMs in late infection. Simultaneously, PRRSV infection significantly increased the transcription of interferon-stimulated gene 15 (ISG15), ISG56, and 2′, 5′-oligoadenylate synthetase 2 (OAS2) in PAMs. In addition, our results showed that PRRSV infection in PAMs via the ADE pathway not only significantly decreased the synthesis of IFN-γ, IFN-λ1, IFN-λ3, and IFN-λ4 but also significantly enhanced the generation of transforming growth factor-beta1 (TGF-β1). Our results also showed that the ADE of PRRSV infection significantly reduced the mRNAs of ISG15, ISG56, and OAS2 in PAMs. In conclusion, our studies indicated that PRRSV-ADE infection suppressed innate antiviral response by down-regulating the expression levels of type II and III IFNs, hence facilitating viral replication in PAMs in vitro. The ADE mechanism illustrated in the present study furthered our understanding of pathogenesis following PRRSV infection mediated by antibodies.